Analisis Perputaran Kas, Perputaran Piutang, dan Perputaran Persediaan terhadap Kinerja Keuangan: Studi Kasus pada Perusahaan Manufaktur Subsektor Food and Beverage Tahun 2020-2022 di Bursa Efek Indonesia - Wulandari, Ayu; Akhirruddin, Anita (IAI Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of cash turnover, accounts receivable turnover and inventory turnover on the financial performance of the food and beverage sub-sector listed on the Indonesia Stock Exchange (BEI) in 2020-2022. This research uses a quantitative descriptive method using the SmartPLS Version 3.0 application in the data processing process during the research period. The population in this study are food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022. The sampling technique used the purpose sampling method which resulted in 33 companies being sampled. The data used is secondary data, where cash turnover, receivables turnover and inventory turnover are independent variables, while Return On Equaty (ROE) is the dependent variable. The analysis method in this research uses R-Square, F-Square, Q2, Model Fit, and Hypothesis Testing. The results of this research show that (1) Cash turnover has a positive effect on Return On Equaty (ROE) in food and beverage sub-sector manufacturing companies on the IDX.(2) Receivables turnover has a negative effect on Return On Equaty (ROE) in food and beverage sub-sector manufacturing companies on the IDX. (3) Inventory turnover has a negative effect on Return On Equaty (ROE).